Comprehensive Analysis of the Global Protein Changes That Occur During Salivary Gland Degeneration in Female Ixodid Ticks Haemaphysalis longicornis - Wang, Hui; Zhang, Xiaoli; Wang, Xiao; Zhang, Baowen; Wang, Minjing; Yang, Xiaolong; Han, Xuying; Wang, Rui; Ren, Shuguang; Hu, Yuhong; Liu, Jingze (Frontiers in Physiology, 2019)
Ticks are notorious blood-sucking arthropods that can spread a variety of pathogens and cause great harm to the health of humans, wildlife and domestic animals. The salivary glands of female ticks degenerate rapidly when the ticks reach critical weight or become engorged, which can be caused by hormones and by the synergistic effects of multiple proteins. To explore the complex molecular mechanisms of salivary gland degeneration in ticks, this study applies iTRAQ quantitative proteomic technology for the first time to study changes in protein expression in the salivary glands of female Haemaphysalis longicornis during the process of degeneration and to search for proteins that play an important role in salivary gland degeneration. It was found that the expression of some proteins associated with energy production was continuously down-regulated during salivary gland degeneration, while some proteins associated with DNA or protein degradation were consistently up-regulated. Furthermore, the expression of some proteins related to cell apoptosis or autophagy was also changed. These proteins were knocked down by RNAi to observe the phenotypic and physiological changes in female ticks. The results showed that the time required for engorgement and the mortality rates of the female ticks increased after RNAi of F0F1-type ATP synthase, NADH-ubiquinone oxidoreductase, cytochrome C, or apoptosis-inducing factor (AIF). The corresponding engorged weights, oviposition amounts, and egg hatching rates of the female ticks decreased after RNAi. Interference of the expression of AIF in engorged ticks by RNAi showed that the degeneration of salivary glands of female ticks was slowed down.